Penerapan Model Guided Inquiry Learning dalam Pembelajaran IPA: Respon Guru dan Siswa - Muhammad Minan Chusni (Nusa Putra University, 2022)
The learning process in the classroom can take place effectively if there is interaction between teachers and students. The interaction can be in the form of a response given by the teacher to student questions or vice versa. This study aims to determine the response of teachers and students after applying the Guided Inquiry Learning (GIL) model in science learning. The method used in this study is descriptive qualitative, namely describing the responses of teachers and students based on the answers to the questionnaire. The subjects in this study were students from class VII at one of the State MTs in Sleman Regency for the 2020/2021 academic year. Data were collected using a questionnaire to see the responses of students and teachers, as well as an interview format to see the teacher's response to learning. Based on the answers to the questionnaire, it can be seen that teachers and students gave positive responses to the application of the GIL model in science learning seen from the average score of teacher responses obtained through the questionnaire which was categorized as very interesting, the average score of student activity in each meeting and the average score of student responses obtained through The categorized questionnaire is very interesting.